PENINGKATAN PARTISIPASI SISWA SD NEGERI TULANG AMPIANG DESA PEMECUTAN KAJA DALAM PENAGULANGAN DBD BERBASIS MASYARAKAT - Darwata, Darwata; Duana, K.; Artawan, Artawan; Suarjana, Suarjana; Utami, A.; M, Hary. (Buletin Udayana Mengabdi, 2012)
ABSTRACT Dengue Haemoragic Fever (DHF) is an infected disease caused by dengue virus with aedes aegypti mosquito as the vector. in Bali Province the case of DHF always increases every year and the data of 2006 show that there were 5.054 cases and the Case Fatality Rate was 0,63%. In order to decrease the DHF case, many methods have been done by the government, such as eradication of mosquitos nest with 3M method (“menutup, menguras, mengubur”), public health illumination, massive fogging , abatitation etc. However those program don’t indicate the optimum result. Other program has been growing up is increasing the participation of public groups. One of that is increasing the participation of basic school student to decrease DHF disease by giving the student knowledge abaut disease, prevention, and how to avoid the DHF disease.